2020
DOI: 10.1080/16878507.2020.1742443
|View full text |Cite
|
Sign up to set email alerts
|

Narrow band ultraviolet B therapy deactivates Th1/Th17 pathway and activates Th2 cytokines secretion in Egyptian psoriatic arthritis patients

Abstract: Narrow band ultraviolet B therapy deactivates Th1/Th17 pathway and activates Th2 cytokines secretion in Egyptian psoriatic arthritis patients,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…Experimentally, administration of IL-10 resulted in shift-type 1 cytokines to type 2 cytokines. In addition, the treatment effect of ultraviolet light on the modulation of inflammation by up-regulation of the IL-10 in keratinocytes has been previously shown [30]. On the other hand, decreasing the level of IL-10 has been demonstrated to consider a critical way to induce disease flare-ups in the psoriatic skin [31].…”
Section: Discussionmentioning
confidence: 98%
“…Experimentally, administration of IL-10 resulted in shift-type 1 cytokines to type 2 cytokines. In addition, the treatment effect of ultraviolet light on the modulation of inflammation by up-regulation of the IL-10 in keratinocytes has been previously shown [30]. On the other hand, decreasing the level of IL-10 has been demonstrated to consider a critical way to induce disease flare-ups in the psoriatic skin [31].…”
Section: Discussionmentioning
confidence: 98%
“…NB-UVB suppresses type I and type II interferons (IFNs), and T helper (Th) 17 signaling pathways 13 . NB-UVB treatment suppresses serum levels of psoriasis-driving cytokines, such as tumor necrosis factor (TNF)-α, IL-8, IL-12, IL-17, IL-22, IL-23, and IL-34 and elevates the levels of IL-10, an anti-inflammatory cytokine, in patients with psoriasis 14,15 . Moreover, NB-UVB treatment significantly suppresses the mRNA levels of nuclear factor-kappa-B inhibitor zeta, serpin family B member 4 (SERPINB4), autophagy related 13, and cathepsin S in the edges of psoriatic plaques 16 and may attenuate TLR-3/4/9 activity in psoriatic plaques 17 .…”
mentioning
confidence: 99%
“…In a study involving 80 patients diagnosed with psoriasis, NB-UVB was shown to significantly reduce serum interleukin (IL)-12, IL-17, and IL-23 levels, thus deactivating the T-helper-1 and T-helper-17 pathways. 18 In another study, NB-UVB-treated psoriasis patients had decreased levels of IL-1b, IL-2, IL-5, and IL-6, along with elevated levels of the anti-inflammatory cytokine IL-10. 19 Ultraviolet B causes Langerhans cells to migrate from the epidermis, thereby reducing their numbers and functions in the epidermis, but NB-UVB is less potent in inducing this effect compared to broadband ultraviolet B.…”
Section: Discussionmentioning
confidence: 96%